Pemberdayaan Daur Ulang Dalam Mengelola Dan Pemanfaatkan Sampah Plastik TPS - Egi Ateta Barus; Khairani Aprilia; Kiki Renhardi Napitupulu; Syukri Hidayat (Fakultas Teknik Universitas Cenderawasih, 2023)
Management and utilization of community plastic waste at TPS is one of the efforts to lessen the bad effect of plastic waste at the environment. This observe goals to determine the management and utilization activities of network plastic waste at TPS. This studies uses qualitative studies strategies with a case have a look at technique. The object of research is: TPS Jl. Ambil no 83 kelurahan Sidorejo hilir kec Medan tembung. TPA Air Terjun Di Medan Marelan kelurahan bandar selamat. Bank sampah karya mitra jl. Datuk kabu, bandar klippa, kec. Percut Sei Tuan, kabupaten Deli Serdang. The results showed that the management and utilization of community plastic waste at the TPS was still not optimal. Plastic waste management activities at TPS are only limited to collection and transportation to the landfill. Plastic waste utilization activities at TPS have not been carried out optimally. Some factors that hinder the management and utilization of community plastic waste at TPS include: Lack of public awareness about the importance of managing and utilizing plastic waste waste; Lack of support from the government and private parties; Lack of facilities and infrastructure for managing and utilizing plastic waste waste. Based on the results of this study, it is recommended to: Increase public awareness about the importance of plastic waste management and utilization; Increase support from the government and the private sector; Improve facilities and infrastructure for the management and utilization of plastic waste waste.